Peran pendidikan kewarganegaraan dalam membentuk ai literacy dan etika digital di era artificial intelligence - Seftian Wahyu Ningtias; Novita Dwy Khairunnisa; Marvela Putri Angraeni; Disya Nabila Hana Mardiah (Universitas PGRI Madiun, 2026)
The rapid development of Artificial Intelligence (AI) has significantly transformed various aspects of human life, particularly in the field of education. This phenomenon requires individuals, especially students, to possess AI literacy and a strong understanding of digital ethics to use technology wisely, critically, and responsibly. This article aims to examine the role of education in improving AI literacy and promoting digital ethics in the era of Artificial Intelligence. The study employs a literature review method by analyzing various scientific sources related to education, AI literacy, and digital ethics. The findings indicate that education plays a strategic role in equipping learners with knowledge about how AI works, developing critical thinking toward AI-generated information, and fostering the ability to use AI ethically. Furthermore, education contributes to instilling values of responsibility, academic integrity, personal data protection, and awareness of the social impacts of AI technologies. The integration of AI literacy and digital ethics into the learning process is essential for preparing a generation that is not only technologically competent but also possesses strong moral character and responsibility in facing future developments in Artificial Intelligence.